Respiratory syncytial virus infection in a selected sample of infants hospitalized for lower respiratory tract infection in Lithuania and Estonia - Drazdienė, Nijolė; Laan, Mari; Zaikauskienė, Jolanta; Usonis, Vytautas (Acta medica Lituanica, 2018)
Background. The study presents data on a sample of children under one year of age hospitalized with lower respiratory tract infections (LRTIs) in Lithuania and Estonia. Subjects and methods. This large, retrospective, cross-sectional, observational epidemiologic survey was conducted in 12 countries in Central and Eastern Europe. Eligible subjects were under one year of age, hospitalized for LRTIs, for whom RDT (Rapid Diagnostic Test) was performed. Physicians completed questionnaires at discharge or on the first check-up visit after hospitalization. To test for RSV, the immunochromatographic method was used in Lithuania, and immunofluorescense or the PCR methods were applied in Estonia. Results. In two countries, 482 patients fulfilling the definition of a LRTI case (i.e., children below one year of age hospitalized with a diagnosis of bronchiolitis and/or pneumonia) were enrolled during two consecutive RSV seasons. Bronchiolitis was the most common diagnosis (84%). In Lithuania and Estonia, 36.6% and 83.3% of cases were conscious at admission. RSV was confirmed in 87.3% and 54.2% of tested LRTI cases in Estonia and Lithuania, respectively. Intensive care unit hospitalization was required for 9.1% of LRTI cases in Lithuania and for 3.1% of cases in Estonia. Supplemental oxygen was required for 23.2% and 31.6% in cases in Lithuania and Estonia, respectively. In Lithuania, complete recovery at discharge was assessed for 35.8% of LRTI cases and improvement in 62.2% of cases. In Estonia, all LRTI cases were improved at discharge and there were no complete recoveries. Conclusion. RSV was prevalent among children hospitalized for LRTI in Lithuania and Estonia; bronchiolitis was the most common diagnosis in hospitalized patients.